Pengembangan Ide Kerja Sosial Sebagai Bentuk Pidana Alternatif di Indonesia - Sani Siti Aisyah (Jurnal Kriminologi Indonesia, 2018)
This thesis discusses the development of community service idea as an alternative punishment within the framework of policy analysis, especially the analysis of the policy agenda. The policy agenda of community service is contained in the Draft Penal Code (RUU KUHP) as the principal punishment which is essentially a criminal procedure as an alternative to imprisonment. The existence of the social work policy agenda in the Criminal Code Bill affects researchers to explore more information or knowledge related to social work. For this purpose, the analysis of the policy agenda of the formulation of the problem is appropriately used because the formulation of the problem can supply knowledge relevant to the policy questioning the assumptions underlying the definition of the problem. This study is a qualitative research with explorative type. Data collection techniques used was literature studies and in-depth interviews with ten expert sources. The results of this study indicate that the development of community service as an alternative punishment, globally, takes place rapidly with international arrangements such as Tokyo Rules and Beijing Rules. Furthermore, the relevant knowledge to be presented within the framework of developing community service ideas as alternative punishment in Indonesia is the main goal of community service order; the appropriate types of crime are responded with community service order; form of community service; the applicability of community service order in Indonesia and the benefits of community service order. This study concludes that the main goal of community service order is restoration and rehabilitation; the types of crimes that can be responded to with social work penalties must be seen from the reality of crime and the reality of crime events; and the form of community service order should be designed to meet the main goals of community service order, rehabilitation and restoration